PENGARUH KEPERCAYAAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA USAHA JAYA PERABOT DI BUKITTINGGI - Anjaya, Fanny Agarista; Yulasmi, Yulasmi; Sopali, Mardhatila Fitri (Journal of Information System, Applied, Management, Accounting and Research, 2024)
This research aims to find out how much influence Trust and Price have on Purchasing Decisions through Customer Satisfaction as an intervening variable at Usaha Jaya Perabot in Bukittinggi. By distributing questionnaires to 50 respondents. The data analysis methods used are Outer Model analysis, Avarage Variance Extracted (AVE), Reliability Research, and Inner Model (Structural Model) testing using Smart PLS 3. Data collection methods are through surveys and distributing questionnaires to consumers as respondents. The results of the research show that there is a positive and significant influence between Price on Customer Satisfaction at Usaha Jaya Perabot in Bukittinggi, there is a positive and insignificant influence between Price on Purchasing Decisions at Usaha Jaya Perabot in Bukittinggi, there is a positive and significant influence between Trust and Customer Satisfaction at Usaha Jaya Perabot in Bukittinggi, there is a positive and insignificant influence between Trust on Purchasing Decisions at Usaha Jaya Perabot in Bukittinggi, there is a positive and significant influence between Customer Satisfaction on Purchasing Decisions at Usaha Jaya Perabot in Bukittinggi, Price mediates the Purchasing Decision through Customer Satisfaction at Usaha Jaya Perabot in Bukittinggi, Trust mediates Purchase Decisions through Customer Satisfaction at Usaha Jaya Perabot in Bukittinggi.